Efficacy of PGF2α, Calcium, Phosphorus, Oxytetracycline and Meloxicam on Fetal Membrane Retention and Postpartum Ovarian Activity in Buffaloes - Indurkar, Sandeep; Tiwari, Rajendra Prasad; Mishra, Girish Kumar; Dubey, Meenu (The Indian Journal of Animal Reproduction, 2022)
Present study was conducted on buffaloes (n=24) which were classified into two groups. In group I, 12 buffaloes after normal calving were randomly classified in treatment (n=6) and control (n=6) sub groups. Whereas in group II, 12 buffaloes after normal calving having RFM/ROP 12 hours after calving were randomly classified in treatment (n=6) and control (n=6) sub groups. In group I and II , the buffaloes in treatment group were administered Dinoprost (25 mg); Meloxicam @0.5 mg/kg body wt., Oxytetracycline @5 mg/kg body wt. i/m and calcium i/v immediately after and after 12 hours of calving, respectively. However, the buffaloes in control group were not given any treatment.There was lower incidence of RFM (16.66% vs 50.00%; P<0.05); early expulsion of fetal membranes (4.05±0.31 vs 4.66±0.99h; P>0.05), early disappearance of fetid discharge (1.83±0.10 vs 2.66±0.33 days; P>0.05), early disappearance of muco-purulent discharge (3.25±0.65 vs 4.66±0.61 days; P>0.05), early uterine involution (32.83±4.43 vs 36.00±6.91 days, P<0.05) and early resumption of ovarian activity (100.16±3.19 vs 109.83±6.34 days; P<0.05) in treatment than control group in the buffaloes of Group I. There was low incidence of RFM in treatment and control groups (00.00% vs 16.66%), early expulsion of fetal membrane (5.33±0.38 vs 8.3±0.86 h; P <0.05), early disappearance of fetid discharge (5.13±0.54 vs 7.16±0.95 days; P>0.05), early disappearance of muco-purulent discharge (5.00±0.52 vs 8.00±0.74 days; P<0.05), early uterine involution (34.00±0.62 vs 44.5±1.57 days; P <0.01) and early resumption of ovarian activity (103.66±2.09 vs 125.33±5.64 days, P<0.01) in treatment than control in the buffaloes of Group II with RFM 12 hours after calving. It could be concluded that immediate treatment regimen after calving reduces the incidence of retention of fetal membrane in buffaloes.